2019
DOI: 10.2217/cnc-2019-0008
|View full text |Cite
|
Sign up to set email alerts
|

Baseline profiles of auditory, vestibular, and visual functions in youth tackle football players

Abstract: Aim: Neurosensory tests have emerged as components of sport-related concussion management. Limited normative data are available in healthy, nonconcussed youth athletes. Patients & methods/results: In 2017 and 2018, we tested 108 youth tackle football players immediately before their seasons on the frequency-following response, Balance Error Scoring System, and King-Devick test. We compared results with published data in older and/or and nonathlete populations. Performance on all tests improved with age. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…29,30 Younger athletes and those with a lower SES also demonstrated slower K-D test times in the current study. White-Schwoch et al 48 found that K-D test times improved with increasing age among youth football players but did not observe an association with SES. In this study by White-Schwoch et al, SES was approximated by referencing a participant's zip code to US Census data of median income for that area and thus did not consider individual-level SES.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…29,30 Younger athletes and those with a lower SES also demonstrated slower K-D test times in the current study. White-Schwoch et al 48 found that K-D test times improved with increasing age among youth football players but did not observe an association with SES. In this study by White-Schwoch et al, SES was approximated by referencing a participant's zip code to US Census data of median income for that area and thus did not consider individual-level SES.…”
Section: Discussionmentioning
confidence: 94%
“…Several variables have been found to potentially affect baseline concussion testing, including sex, 5 , 8 - 12 , 39 , 42 , 43 age, 5 , 8 , 11 , 18 , 19 , 43 , 48 race, 18 , 44 , 46 and a history of learning disabilities 8 , 10 , 13 , 18 , 29 , 31 , 32 , 38 and mental health conditions. 10 , 11 , 32 , 45 , 47 Many of these previous studies were conducted in collegiate athlete populations, and thus less is known about the associations of demographic factors with baseline concussion testing in other populations, such as youth athletes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To fill this clinical gap, FFR elicited with a 40-ms /da/ stimulus at a relatively high repetition rate (e.g., 10.9/s), also known as BioMARK (Biological Marker for Auditory Processing), was developed. 27 BioMARK, and FFRs in general, have been found to be sensitive to a variety of disorders ranging from dyslexia, 28,29 autism, 30,31 auditory processing disorder (APD), [32][33][34][35] and concussion 36 and exhibit potential for use in the clinics.…”
Section: Use Of Auditory Evoked Potentials In Diagnosticsmentioning
confidence: 99%